Natural and Social Conditions for Economic Development: Case Study Northeastern Montenegro - Goran Rajovic; Jelisavka Bulatovic (Hyperion Economic Journal, 2013)
This paper analyzes the natural and social conditions for the development economy in northeastern Montenegro, in the example municipalities Berane, Andrejevica and Plav in the geographical context of its utilization and use. Spatial distribution of the economy is determined by the natural and social conditions. The natural conditions in terms of the economy are of particular significance relief, climatic and hydrographic conditions, soil... According to degree benefits of natural conditions extracted are three relatively homogeneous regions. That is, which rational production of this part of north-eastern Montenegro, can be organized taking into account the natural conditions and the level of socio-economic development. For collocation and the structure of the economy have an important role in the social conditions which the economy is formed. Our research the records clearly pointed to the forefront some very obvious problems: first, is related to the population, especially in workforce, respectively, for the aging; second, that there is a strong migration of people whose intensive processes of differentiation and left behind an unfavorable structure of the population - age and education what the any negative impact on economic development; third, the characteristics of land area, its small size, inadequate and outdated processing, low technical capacity. The natural resources of this part of north-eastern Montenegro, as well as the population as a factor of economic development need to have met: economic, social, developmental organizational and management dimension to be on benefit the present, but also future generations